2001
DOI: 10.5032/jae.2001.04032
|View full text |Cite
|
Sign up to set email alerts
|

Ohio 4-H Agents' Perceptions Of The Level Of Importance And Frequency Of Use Of The Eighteen Components Of The Gems Model Of Volunteer Administration

Abstract: Volunteers seek service opportunities that are interesting, rewarding, enjoyable, and provides a learning experience. Volunteers search for positions that provide them with the experiences they desire. With this in mind, administrators of volunteer-driven programs and agencies need to consider the most appropriate ways to manage volunteer programs that maximize volunteer contributions to serve the organization and its programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Numerous studies have identified the deficiencies of Extension professionals in coordinating volunteers and volunteer programs (Collins, 2001;Culp & Kohlhagen, 2001;Deppe & Culp, 2001;Hange, Seevers & VanLeeuwen, 2002).…”
Section: Introduction/theoretical Frameworkmentioning
confidence: 99%
“…Numerous studies have identified the deficiencies of Extension professionals in coordinating volunteers and volunteer programs (Collins, 2001;Culp & Kohlhagen, 2001;Deppe & Culp, 2001;Hange, Seevers & VanLeeuwen, 2002).…”
Section: Introduction/theoretical Frameworkmentioning
confidence: 99%
“…The typical Agent in Kentucky was nearly identical to that of an Ohio agent as described by Deppe & Culp (2001) except for their level of education; Ohio 4-H Agents were required to complete a Master's degree, Kentucky Agents were required to hold a Bachelor's degree, at a minimum.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the rank order for frequency of use was similar to that of competence, the scores had more fluctuation and a wider range of distribution across the scale. Deppe and Culp (2001) reported that Ohio 4-H Agents ranked the order for the 18 phases of GEMS for their perceived frequency of use as Providing Resources, Orienting, Selecting, Recognizing, Screening, Engaging, Teaching, Protecting, Recruiting, Motivating, Supervising, Retaining, Disengaging, Job Description, Identifying, Redirecting, Needs Assessment and Evaluating. The categories were ranked as Educate, Mobilize, Generate and Sustain according to the perceived frequency of use.…”
Section: Discussionmentioning
confidence: 99%
“…Development professionals in the Cooperative Extension Service have five years experience or less as both 4-H Youth Development and volunteer leadership development professionals (Deppe, 1998;Kohlhagen, 1999).…”
Section: Studies From Ohio and Kentucky Found That Half Of The 4-h Youthmentioning
confidence: 99%
“…The primary focus of this article is the identification of the differences in the levels of education, occupation, and college major of the volunteer leaders, field staff and state staff, or faculty, along with the implications for leadership education that these differences will have for the volunteer leaders. (Deppe, 1998;Kohlhagen, 1999).…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%